Communicative patterns and politeness strategies in ‘sms your views’ column in a local English daily / Shanthi Karappan - Shanthi, Karappan (2016)
This study investigates the linguistics forms, communicative features and language use in ‘SMS Your Views’ column of The Star daily. A collection of 1030 text messages sent by the readers of The Star daily retrieved from the daily’s online portal. Three frameworks were used in this study. The frameworks are by Ling(2005), Thurlow(2003) and Brown and Levinson(1987). Ling’s framework is used to investigate the linguistics forms of the text messages. Thurlow’s communication theme and orientation framework is used to identify the communicative pattern of the messages. Brown and Levinson’s Politeness theory is used to examine the politeness strategy in the messages. Investigation on linguistics forms identified that the use of abbreviations in these messages is not new or incomprehensible. The messages were also identified containing complex message structure, minimal violation of capitalization usage, rare punctuation usage and the use of Malay acronyms as the most preferred code-switching pattern. The communicative pattern in the messages was identified with only seven communication thematic content. In sequence of order, they are Informational Practical, Informational Relational, Social Arrangement, Practical Arrangement, Friendship Maintenance, Phatic and Chain Messages. The communication orientation identified is more high intimacy high relational orientation. Lastly, investigation of language use in terms of politeness strategy identified that the use of positive politeness strategy is prominent. This is followed by bald on record strategy, negative politeness strategy and off record strategy. This study reflects on Malaysian diversity in embracing technology into their daily life. It reflects the capability, creativity, and hospitality of local texters in indulging themselves openly by texting to a publicly accessible social media.